Genki Textbook Analysis for a Mexican University Context: Realities and Challenges Faced by both Teachers and Students - Muro Samano, Baudelio (México y la Cuenca del Pacífico, 2020)
This project was written out of the necessity that CELEX students had regarding their Japanese textbooks (The Genki Series) being written in English, and how such a situation happens in a Mexican university context. The following situations were analyzed: the state of the Genki book used in the CELEX programs of the University of Guadalajara, the students’ English knowledge status needed to work with the material, and what CELEX teachers should consider when adapting, re-purposing, and/ or replacing this textbook in their classes. These issues were tackled through a qualitative kind of research as both a case study and a need analysis evaluation (from which an online survey was applied to know the students’ opinions in certain topics). The results were mixed among the students concerning their personal language competence perception, feelings towards having a Japanese textbook in English, as well as opinions concerning teachers’ material development complementing the book’s contents.